Civil disobedience and deliberative democracy - Smith, William (London ; New York : Routledge, 2013)
"Civil disobedience is a public, nonviolent, conscientious yet political act, contrary to law, carried out to communicate opposition to law and policy of government. This book presents a theory of civil disobedience that draws on ideas associated with deliberative democracy"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Civil disobedience; Deliberative democracy; Electronic books